Simultaneous Insertion of Two Expression Cassettes into Adenovirus Vectors - Xavier Danthinne (BioTechniques)
We have designed AdenoQuick, a fast and versatile method to construct first-generation adenoviral vectors that contain one or two transgenes in the E1 and/or the E3 region. The method is based on the reconstitution of the entire genome of the desired recombinant virus in E. coli and the subsequent transfection of the DNA in a helper cell line. Since the construction of large adenoviral plasmids is generally difficult and therefore rebuffing for inexperienced researchers, we have optimized the cloning strategy by using bacterial positive-selection markers and a set of specific restriction enzymes that allow for directional cloning. The system is 99% efficient and allows one to insert simultaneously two expression cassettes into the E1 and E3 regions of the adenovirus genome.